Noncompliance with tuberculosis treatment by patients at a tuberculosis and AIDS reference hospital in midwestern Brazil - Rabahi,Marcelo Fouad (2002)
Introduction: In developing countries, there is little information about the risk factors that predict noncompliance with tuberculosis (TB) treatment in hospitals. Objective: This study analyzes possible factors associated with noncompliance with TB treatment among patients treated at HAA. Design: A retrospective cohort study was made including all patients who initiated TB treatment at HAA, from January to December 1998. A standard form was used to review medical records and to collect data on each patient. This data was evaluated in comparison with data from the state TB control program. Results: Of the 341 patients included in the study, 186 (61.2%) were considered cured and 67 (22%) were non-compliant. The factors associated with noncompliance were: previous anti-TB treatment (RR = 1.95, 95% CI 1.29 to 2.93), prescription of drugs other than the standard first-line regimen proposed by the Brazilian Health Ministry (Rifampin + Isoniazide + Pyrazinamide) (RR = 0.54, 95% CI 0.35 to 0.83), the need for hospitalization (RR = 2.19, 95% CI 1.46 to 3.29) and non-inclusion in the hospital's TB Control Program for treatment follow up (RR = 0.54, 95% CI 0.35 to 0.82). Setting: Anuar Auad Hospital (HAA) - Goiânia, Goiás, Brazil. Conclusion: Our results indicate the importance of establishing Tuberculosis Control Programs in hospitals, while paying special attention to patients with risk factors for noncompliance with TB treatment.